2018
DOI: 10.1021/acs.macromol.7b02663
|View full text |Cite
|
Sign up to set email alerts
|

Combination of RAFT and Pd(II)-Initiated Isocyanide Polymerizations: A Versatile Method for Facile Synthesis of Helical Poly(phenyl isocyanide) Block and Star Copolymers

Abstract: We report a new method for facile synthesis of block and star copolymers composed of helical poly(phenyl isocyanide) and polyacrylate segments via combination of Pd(II)initiated isocyanide polymerization and reversible addition− fragmentation chain transfer (RAFT) controlled radical polymerization. First, an alkyne−Pd(II) complex containing benzyl trithiocarbonate substituent was designed and synthesized. The Pd(II) moiety of the complex can catalyzed the living polymerization of phenyl isocyanides, while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 57 publications
(90 reference statements)
0
39
0
Order By: Relevance
“…However, the ATRP did not take place even at higher temperature (100 °C in toluene) or longer reaction time. Probably, the ATRP process was interfered by the CN double bonds in the polyisocyanide segment . To confirm the negative effect of the CN double bonds on ATRP, the classical ATRP homopolymerization of 1a was carried out with additional poly‐ 2a 50 .…”
Section: Resultsmentioning
confidence: 99%
“…However, the ATRP did not take place even at higher temperature (100 °C in toluene) or longer reaction time. Probably, the ATRP process was interfered by the CN double bonds in the polyisocyanide segment . To confirm the negative effect of the CN double bonds on ATRP, the classical ATRP homopolymerization of 1a was carried out with additional poly‐ 2a 50 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, RAFT polymerization is considered to be an important and effective way to prepare multifunctional copolymers, which is widely used in materials science, biology, electronics, etc. [26][27][28][29][30][31][32] For example, amphiphilic block copolymer p(HEMA-b-Azo-IEM) was successfully prepared by RAFT polymerization, in water solution, which selfassembled into micelles, and its size and shape changed with the different light irradiation (visible/UV light). 33 Phenylboronic acid derivatives have been widely used in the synthesis of glucose-sensitive materials in the eld of biomedicine due to their specic interaction with biological molecules such as glucose and glycoproteins.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported synthesis of poly(phenyl isocyanide) derivatives with optical activity and a helical structure. [ 5–10 ] This required controlling the winding direction of the helix, as the orientation of the chiral side chain in the polymer dictates main‐chain helicity and macroscopic morphology of the polymer. Preparation of chiral polyisocyanides using a chiral oligomer as an initiator was previously employed to obtain chiral polymers, with the use of liquid crystal solvent isocyanide polymerization allowing the formation of one‐handed, optically active, helical polyisocyanides capable of analysis by atomic force microscopy and molecular calculations.…”
Section: Introductionmentioning
confidence: 99%